Facilitating international animal welfare standards implementation in national contexts: The role of intermediaries in Brazilian pig production. (February 2022) - Vilas-Boas, Jean; Klerkx, Laurens; Lie, Rico
Abstract: International agreements have been adopted in recent years to disseminate animal welfare standards worldwide, similar to the situation for environmental and social sustainability standards. Scholars who have analyzed such initiatives argue that this calls for contextualized strategies for a successful implementation of international animal welfare standards in specific settings, also emphasizing the relevance of individuals and institutions who function as intermediaries in these complex situations of change. However, previous studies do not provide empirical insights into how different intermediaries work in relation to international animal welfare standards implementation in national contexts. Focusing empirically on the implementation of EU animal welfare directives in Brazilian pig production, this paper aims to connect the standards implementation and intermediation literatures to deepen the understanding of how a network of intermediaries formed and acted as an 'ecology of intermediaries' to facilitate the implementation process for international animal welfare standards. The paper aims to enrich debates on how to develop contextualized strategies that can translate recognized international regulations into practical animal welfare improvements. Our findings provide evidence that collective intermediation efforts are pivotal in addressing demands (such as translation, adaptation, regulation) that emerge from the complex situation of change provoked by the implementation of international animal welfare standards in national contexts. The main implication of our study for theory on standards implementation is that the operationalization of a contextualized strategy linked to international animal welfare standards implementation is composed of a normative dimension and a technological dimension and that, to achieve their desired outcome, contextualized strategies also rely on connected and complementary intermediation actions. Highlights: Animal welfare standards implementation requires contextualized strategies. Intermediation is pivotal in operationalizing animal welfare standards implementation. Intermediaries formed an ecology that facilitates standards implementation. Contextualized implementation strategies have normative and technological dimensions. Contextualized strategies also rely on connected and complementary intermediation.